Analisis Dan Evaluasi Implementasi Sistem ERP (Enterprise Resources Planning) Pada PT Petrokopindo Cipta Selaras - Nidya Puspithasari; Nur Fadhilah; Nur Hayati (Lembaga Peneliian dan Pengabdian Masyarakat (LPPM) Universitas Islam Madura (UIM), 2023)
Utilization of Information Technology is a solution for PT Petrokopindo Cipta Selaras in facing this increasingly competitive business environment. In order to realize the company's commitment to both corporate value and customer value, PT Petrokopindo Cipta Selaras implements an ERP (Enterprise Resources Planning) system to increase the effectiveness of company management. The purpose of this study is to analyze and evaluate the implementation of the ERP system used by PT Petrokopindo Cipta Selaras. The method used is using a qualitative approach with the action research method. This research was conducted by direct observation and interviews with users of the company's ERP system. The results of the study concluded that with the implementation of the ERP system in general the implementation has been going well, this can be seen from the implementation of the ERP system, it is easier for companies to make business decisions because the existing data is integrated, updated and accurate. However, the company also still needs to monitor the system because there are several obstacles that make the ERP system not run optimally.